Urban Proximity, Agricultural Potential and Rural Non-farm Employment: Evidence from Bangladesh - Deichmann, Uwe (2012)
This paper presents empirical evidence on the relative importance of farm and urban linkages for rural non-farm employment in Bangladesh. The results suggest that people are more likely to be employed in well-paid wage employment and self-employment in the non-farm sector if they are closer to urban centers. Those who are further away from such centers are even less likely to be in well-paying non-farm jobs if they are living in areas with greater agricultural potential. The empirical results highlight the need for improved connectivity of regions with higher agricultural potential to urban centers for non-farm development in Bangladesh.